2011
DOI: 10.1111/j.1365-3024.2011.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an ELISA for canine leishmaniasis immunodiagnostic using recombinant proteins

Abstract: The present work describes the isolation and purification of two Leishmania chagasi (= syn. Leishmania infantum) recombinant proteins, rLci2B and rLci1A, and their use in the development of an immunoassay for the diagnostic of canine leishmaniasis. After protein expression and cell disruption, rLci2B was purified by immobilized metal affinity chromatography followed by size exclusion chromatography, whereas rLci1A, expressed as an inclusion body, was treated with urea and purified by anion-exchange chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…A previous study demonstrated that rLci1A and rLci2B offer 96% and 100% sensitivity, with respective specificity rates of 92% and 95% under ELISA against sera from animals with positive parasitological test results [9]. These findings clearly indicate the potential of these selected antigens for use in CVL diagnosis.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…A previous study demonstrated that rLci1A and rLci2B offer 96% and 100% sensitivity, with respective specificity rates of 92% and 95% under ELISA against sera from animals with positive parasitological test results [9]. These findings clearly indicate the potential of these selected antigens for use in CVL diagnosis.…”
Section: Resultsmentioning
confidence: 62%
“…Affinity chromatography was used to purify the rLci1A and rLci2B proteins as previously described [9]. …”
Section: Methodsmentioning
confidence: 99%
“…In the last decades, an increasing number of recombinant protein candidates have been proposed to replace the crude Leishmania antigen (SLA) for the serodiagnosis of leishmaniasis [24], [31]–[34]. Presently, we decided to test the feasibility of using recombinant antigens derived from L. infantum-chagasi for the serodiagnosis of TL.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to increase ELISA specificity in the diagnosis of VL or TL, through the elimination of cross-reactive epitopes, the use of recombinant Leishmania inmunodominant antigens has been evaluated [20], [21]. Many recombinant antigens have been tested for the serodiagnosis of canine or human VL [22][24], however, up to date, few recombinant proteins have been described as promising for the serodiagnosis of human TL [25]. In the present study, we employed a large panel of human sera to test a series of parasite-derived recombinant proteins, using ELISA, aiming at the development of better tool for human TL serodiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The recombinant antigens showed no cross-reactivity with sera from dogs infected with Trypanosoma caninum, Babesia canis and Ehrlichia canis. Cross-reaction against sera from dogs infected with Leishmania braziliensis was observed for rLci1A-based ELISA (11.7%) and for rLci2B-based ELISA (2.9%) [109].…”
Section: • Datmentioning
confidence: 98%